2007
DOI: 10.1002/ceat.200700139
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of SO2Removal from Flue Gas on CuO/Al2O3Sorbent Catalyst

Abstract: The dependence of SO 2 removal on Cu loading, SO 2 concentration, and temperature are studied experimentally on a thermo-balance using a series of CuO/Al 2 O 3 catalysts in the fresh state as well as in a NH 3 -regenerated state. A kinetic study on SO 2 removal is then carried out using a surface model, which assumes the SO 2 removal rate is being controlled by a surface chemical reaction and takes into account the effect of SO 2 adsorption and consumption of surface CuO. The difference in SO 2 removal between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Metal oxides and metal carbonates are the current adsorbents of throw-away processes consist of CaO (lime), MgO,Na2CO3,K2CO3,Fe2O3,etc. The main characteristic of these processes are simplicity of operation and economic efficiency (Gray &Jarvis 2020, Jia et al 2007, Tseng &Wey 2004. Major advantage of sodium carbonate is its ability to remove SO2 at low temperatures (about 200 o C).…”
Section: Background Informationmentioning
confidence: 99%
“…Metal oxides and metal carbonates are the current adsorbents of throw-away processes consist of CaO (lime), MgO,Na2CO3,K2CO3,Fe2O3,etc. The main characteristic of these processes are simplicity of operation and economic efficiency (Gray &Jarvis 2020, Jia et al 2007, Tseng &Wey 2004. Major advantage of sodium carbonate is its ability to remove SO2 at low temperatures (about 200 o C).…”
Section: Background Informationmentioning
confidence: 99%
“…Previous study showed that 5% NH 3 at 400 • C can directly convert SO 2 that is regenerated from catalyst into solid ammonium sulfur salts [139]. The removal efficiencies of SO 2 and NO, respectively, were defined as: [ Much of the literature gave detailed descriptions on the issues of SO 2 and NOx removal [139][140][141][142][143][144][145][146]. Table 5 shows some experimental work available in literature on the simultaneous NOx/SOx removal studies.…”
Section: Simultaneous So 2 /Nox Removal From Flue Gasmentioning
confidence: 99%
“…Previous studies have shown that sulfuric deactivated activated carbon can be heated to above 350 • C, and sulfuric acid is reduced to produce concentrated SO 2 under inert gases or by heating in a reductive gas flow (NH 3 , urea, CO, CH 4 , H 2 ) [7,42]. NH 3 is a favorable reductant for Al 2 (SO 4 ) 3 in contrast to H 2 and CH 4 , due to its regeneration potential on the catalyst at the temperatures of the SO 2 removal (400 • C) [142].…”
Section: Regenerationmentioning
confidence: 99%
“…To further investigate the reaction rate and reaction mechanism, various metal oxides were analyzed for removing SO 2 . Among them, the calcium-based kinetics of desulfurization and regeneration were conducted numerous researches. Similarly, the other researchers carried out the kinetic studies on copper-based and manganese-based sorbents in desulfurization-regeneration cycles. Based on previous research, the possible kinetics reactions in the reactors are presented as follows.…”
Section: Mechanism Of Flue-gas Desulfurization With Cltmentioning
confidence: 99%